The THE IMPLEMENTATION OF ISLAMIC IDENTITY THROUGH ISLAMIC VALUES IN EFL SPEAKING CLASSROOM - Hanif Nurcholish Adiantika (Risâlah, Jurnal Pendidikan dan Studi Islam, 2019)
The present study aims to investigate the implementation of Islamic identity through Islamic values in EFL speaking classroom. It covers the benefits and challenges encountered by teacher and students in integrating Islamic identity through Islamic values in teaching speaking skill. This study utilizes qualitative research by using a case study design. This study was conducted in one private university in Cirebon covering one class of the first semester. The data were gained through observation, interview, and questionnaires. The findings reveal that the implementation of Islamic values is considered to be positive in creating English creating English-based Islamic circumstances, providing a contextual classroom instruction-based Islamic values, and encouraging students’ activeness. However, some challenges are also found in this study namely teacher’s capacity and insufficient English materials with Islamic content. Therefore, regardless the challenges that are also found in this study, it can be asserted that the implementation of Islamic value in EFL speaking classroom offers an alternative method to teach EFL students in university level.